Exergy analysis of syngas production via biomass thermal gasification - Echegaray, Marcelo Eduardo (2016)
Biomass has great potential as a clean, renewable feedstock for producing modern energy carriers. This paper focuses on the process of biomass wastes gasification, where the synthesis gas may subsequently be used for the production of electricity, fuels and chemicals. The gasification process is one of the least-efficient operations in the whole biomass-to-energy technology chain and an analysis of the efficiency of the gasifier alone can substantially contribute to the efficiency improvement of this chain. In this work, biomass wastes from canneries (peach pits) and wine industry (marcs and stalks) used for the syngas production are investigated. Thermodynamic indicators of process performance based on the second law (exergy analysis) was utilized in order to evaluate the effect of different operational parameters (temperature, supply air/stoichiometric air, supply steam/carbon ratio and moisture feed). The exergetic efficiency of the gasification process decreases when the all considered operational parameters increase. The gasification of peach pits shows the maximum values of the exergetic efficiency in all conditions.